Insight on Current Advances in Food Science and Technology for Feeding the World Population - Valoppi, Fabio; Agustin, Melissa; Abik, Felix; Morais de Carvalho, Danila; Sithole, Jaison; Bhattarai, Mamata; Varis, Jutta J.; Arzami, Anis N. A. B.; Pulkkinen, Elli; Mikkonen, Kirsi S. (Frontiers in Sustainable Food Systems, 2021)
While the world population is steadily increasing, the capacity of Earth to renew its resources is continuously declining. Consequently, the bioresources required for food production are diminishing and new approaches are needed to feed the current and future global population. In the last decades, scientists have developed novel strategies to reduce food loss and waste, improve food production and find new ingredients, design and build new food structures, and introduce digitalization in the food system. In this work, we provide a general overview on circular economy, alternative technologies for food production such as cellular agriculture, and new sources of ingredients like microalgae, insects, and wood-derived fibers. We present a summary of the whole process of food design using creative problem-solving that fosters food innovation, and digitalization in the food sector such as artificial intelligence, augmented and virtual reality, and blockchain technology. Finally, we briefly discuss the effect of COVID-19 on the food system. This review has been written for a broad audience, covering a wide spectrum and giving insights on the most recent advances in the food science and technology area, presenting examples from both academic and industrial sides, in terms of concepts, technologies, and tools which will possibly help the world to achieve food security in the next 30 years.